2022
DOI: 10.21203/rs.3.rs-530170/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emerging infectious outbreak inhibits pain empathy mediated prosocial behaviour

Abstract: The pandemic of COVID-19 sets off public psychological crises and impacts social functioning. Pre-pandemic research has shown that empathy exhaustion will happen as the mental resource wears out under long-term distress. While prosocial activities are positively linked to empathy, quantitative research on the pandemic's effect on empathy and prosocial willingness has been insufficiently examined. Prosocial behaviors are carried out during a life-threatening time to promote communication and encourage community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 47 publications
4
6
1
Order By: Relevance
“…For all other questionnaire scores, Group differences were assessed through independent samples t -tests. In particular, the direction of the effects associated with the four empathy subscores of the Interpersonal Reactivity Index (IRI) could be well predicted by the previous study from (Cao et al, 2020) which found decreased scores following the lockdown (except for the Personal Distress subscore which increased). As such, we tested “directional” effects under one-tailed significance for any of the four subscores, thus leading to a one-tailed α error = 0.0125 (corresponding to 0.05/4).…”
Section: Methodssupporting
confidence: 55%
See 2 more Smart Citations
“…For all other questionnaire scores, Group differences were assessed through independent samples t -tests. In particular, the direction of the effects associated with the four empathy subscores of the Interpersonal Reactivity Index (IRI) could be well predicted by the previous study from (Cao et al, 2020) which found decreased scores following the lockdown (except for the Personal Distress subscore which increased). As such, we tested “directional” effects under one-tailed significance for any of the four subscores, thus leading to a one-tailed α error = 0.0125 (corresponding to 0.05/4).…”
Section: Methodssupporting
confidence: 55%
“…Data for only 147 (out of 160) participants were available (73 pre-lockdown and 74 post-lockdown). In particular, we ran independent sample t -tests on the four subscores of the IRI questionnaire, in the attempt to replicate the effects previously reported by Cao et al (2020). We found a significant group (pre- vs post-lockdown) difference only for the empathy concern subscale of the IRI (Davis, 1980), t (145) = 2.40, p (one-tailed) = .009, d = 0.20.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Regarding the fear related to pandemic, our analyses revealed no differences between helpers and non‐helpers. This result is contrary to the findings of previous studies which showed that fear and anxiety were usually related to less prosocial behavior (Cao et al ., 2020; Ye et al ., 2020) and it is more in line with meta‐analytic findings that showed that negative affect and anxiety are not the determimants of prosocial behavior (Thielmann et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cao, Qi, Y Huang et al . (2020) have shown that both trait and state empathy were related to prosocial willingness in the time of COVID‐19 pandemic. Interestingly, they found that the closer to the epicenter of the pandemic (the City of Wuhan) the participants were, the less they were willing to help due to increased anxiety.…”
Section: Introductionmentioning
confidence: 99%